Nucleosome compaction facilitates HP1γ binding to methylated H3K9 - Mishima, Yuichi (Nucleic Acids Res, 2015)
The α, β and γ isoforms of mammalian heterochromatin protein 1 (HP1) selectively bind to methylated lysine 9 of histone H3 via their chromodomains. Although the phenotypes of HP1-knockout mice are distinct for each isoform, the molecular mechanisms underlying HP1 isoform-specific function remain elusive. In the present study, we found that in contrast to HP1α, HP1γ could not bind tri-methylated H3 lysine 9 in a reconstituted tetra-nucleosomes when the nucleosomes were in an uncompacted state. The hinge region connecting HP1's chromodomain and chromoshadow domain contributed to the distinct recognition of the nucleosomes by HP1α and HP1γ. HP1γ, but not HP1α, was strongly enhanced in selective binding to tri-methylated lysine 9 in histone H3 by the addition of Mg(2+) or linker histone H1, which are known to induce compaction of nucleosomes. We propose that this novel property of HP1γ recognition of lysine 9 in the histone H3 tail in different nucleosome structures plays a role in reading the histone code.